Large-particle-size alloy catalyst, preparation method and application thereof
Patent Information
- Application Number
- CN202311129862.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-04
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2043-09-04
AI Technical Summary
[0003]通常情况下,催化剂的粒径越小,催化剂表现出的性能会越高,但是大粒径催化剂的耐久性一般情况下比小粒径催化剂好,目前燃料电池催化剂制备研究中,没有涉及大粒径催化剂的研究,进一步地进行大粒径的催化剂的耐久性以及应用在燃料电池阴极性能的验证几乎没有,因此对大粒径催化剂的研究具有重要的意义
[0020] (1) The preparation method of the large particle size alloy catalyst of the present invention is easy to scale up industrially and has good industrialization prospects.
Smart Images

Figure CN116995250B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of materials preparation technology, specifically relating to a large-particle-size alloy catalyst, its preparation method, and its application. Background Technology
[0002] Proton exchange membrane fuel cells (PEMFCs) have become a focal point in new energy development strategies due to their advantages such as high power density, safety, environmental friendliness, and stable output. As the core material of fuel cells, the catalyst's performance directly affects the power density. Furthermore, the particle size of the catalyst influences mass transfer and electrochemical specific surface area of the catalyst layer; therefore, research on controlling catalyst particle size is of significant practical importance.
[0003] Generally, the smaller the particle size of a catalyst, the higher its performance. However, large-particle-size catalysts generally have better durability than small-particle-size catalysts. Currently, there is no research on large-particle-size catalysts in fuel cell catalyst preparation research, and there is almost no further verification of the durability of large-particle-size catalysts and their performance in fuel cell cathodes. Therefore, research on large-particle-size catalysts is of great significance. Summary of the Invention
[0004] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a large-particle-size alloy catalyst, its preparation method, and its application. The preparation method of this invention increases the particle size of the alloy catalyst through high-temperature calcination, further improving the alloying degree and simultaneously increasing the crystallinity of the particles. This alloy catalyst exhibits excellent oxygen reduction performance, and when used as a film electrode in the cathode side of a proton exchange membrane fuel cell, it demonstrates good polarization performance.
[0005] To achieve the above technical objectives, the technical solution adopted in the embodiments of the present invention is as follows:
[0006] In a first aspect, embodiments of the present invention provide a method for preparing a large-particle-size alloy catalyst, comprising the following steps:
[0007] (1) Raw material mixing: Add the calculated amount of precious metal compound and transition metal powder to the carrier, mix thoroughly and evenly, and then add the mixing agent and mix thoroughly and evenly.
[0008] (2) Particle size growth: The raw materials that are mixed evenly in step (1) are calcined in a mixed atmosphere for 3-18 hours. After calcination, a catalyst precursor with large particle size is obtained.
[0009] (3) Particle size stabilization step: Add 0.5-20L of a stabilizer solution with a concentration of 1-4mol / L to the large particle size catalyst precursor obtained in step (2), stabilize it at 25-80℃ for 1-24h, and then wash and dry it to obtain the alloy catalyst.
[0010] Furthermore, the specific surface area of the carrier described in step (1) is 500-1500 m². 2 / g, using carriers including Ketjen black, nano-graphite, conductive carbon black, mesoporous carbon materials, carbon nanotubes and graphene.
[0011] Furthermore, the noble metal compound mentioned in step (1) refers to a platinum-containing compound including chloroplatinic acid, platinum nitrate, dinitrosodiamineplatinum, and platinum chloride, with a mass ratio of the noble metal element to the carrier of 0.1-1.2.
[0012] Further, the transition metal powder mentioned in step (1) refers to a manganese-containing compound including manganese sulfate, manganese nitrate, manganese acid phosphate, manganese dioxide, manganese carbonate and manganese stearate, with a mass ratio of transition metal element to carrier of 0.03-0.5.
[0013] Further, the mixture in step (1) is one of potassium hydroxide, potassium carbonate, urea, sodium hydroxide, sodium carbonate, sodium bicarbonate and ammonium dihydrogen phosphate or any mixture of the above substances, and the mass of the mixture accounts for 0.01-3% of the total mass of the raw materials.
[0014] Further, the mixed atmosphere mentioned in step (2) is a mixed atmosphere of hydrogen and argon, wherein the volume percentage of hydrogen in the mixed atmosphere is 50 ppm-5%.
[0015] Furthermore, in step (2), the temperature is increased to 900-1300℃ at a heating rate of 5-30℃ / min during roasting.
[0016] Furthermore, the stabilizer solution in step (3) is a mixture of two or more of ethylene glycol, ethanol, hydrochloric acid, nitric acid, citric acid, sulfuric acid, acetic acid and water, with the largest molar amount as the solvent, and the concentration of the stabilizer solution is 1-4 mol / L.
[0017] Secondly, embodiments of the present invention provide a large-particle-size alloy catalyst, which is prepared by the preparation method described in the first aspect. According to the XRD pattern, the particle size of the large-particle-size alloy catalyst is calculated to be ≥12nm using the Scherrer formula.
[0018] Thirdly, embodiments of the present invention provide the application of the large-particle-size alloy catalyst described in the second aspect in fuel cells.
[0019] The beneficial effects of the technical solution provided by the embodiments of the present invention are as follows:
[0020] (1) The preparation method of the large particle size alloy catalyst of the present invention is easy to scale up industrially and has good industrialization prospects.
[0021] (2) The present invention grows the alloy catalyst particles by high-temperature calcination, thereby increasing the particle size of the alloy catalyst, obtaining crystals with higher crystallinity, and improving the crystallinity and particle size of the alloy catalyst.
[0022] (3) The preparation method used in this invention makes the noble metal and transition metal elements more uniformly doped at the micro level, forming an alloy catalyst lattice structure with a higher degree of crystallinity, improving the degree of alloying, and thus exhibiting higher oxygen reduction performance.
[0023] (4) The large-particle-size alloy catalyst prepared by the method of the present invention has better oxygen reduction performance. While the performance is improved, the mass activity hardly decreases after 30,000 cycles of catalyst durability test, and the durability performance is excellent.
[0024] (5) The large-particle-size alloy catalyst prepared by the method of the present invention can improve the contact area of oxygen at the three-phase interface after it is made into a membrane electrode due to its unique large-particle-size particles, thereby further improving the oxygen transport rate and the power generation performance of the membrane electrode.
[0025] (6) The large-particle-size alloy catalyst prepared by the method of the present invention can still be used to prepare a film electrode for application on the cathode side of a fuel cell under the premise of large particle size, and has high polarization performance. Attached Figure Description
[0026] Figure 1 This is a transmission electron microscope (TEM) image of the large-particle-size alloy catalyst prepared in Example 4 of this invention.
[0027] Figure 2 These are comparison diagrams of the X-ray powder diffraction (XRD) characteristic curves of the alloy catalysts prepared in Example 3 and Comparative Example 1 of this invention.
[0028] Figure 3 These are polarization curves of single cells made from the alloy catalysts prepared in Examples 5 and 6 of this invention.
[0029] Figure 4 This is the LSV curve after 30,000 cycles of catalyst durability testing in a three-electrode system. Detailed Implementation
[0030] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0031] Example 1
[0032] A method for preparing a large-particle-size alloy catalyst includes the following steps:
[0033] (1) Grind 5.3g of chloroplatinic acid hexahydrate crystals, 0.5g of manganese sulfate monohydrate and 2g of Cabot XC-72R carbon black carrier thoroughly in a mortar and pestle, then add 2.9g of potassium hydroxide and 0.3g of potassium carbonate mixture and continue grinding and mixing to form a uniform raw material.
[0034] (2) The raw materials that were mixed evenly in step (1) were heated to 900°C for 18 hours at a heating rate of 5°C / min in a mixed atmosphere of argon and hydrogen (the volume ratio of hydrogen in the mixed atmosphere was 5%). After the calcination was completed, a large particle size catalyst precursor was obtained.
[0035] (3) Add 0.5L of 4mol / L hydrochloric acid aqueous solution (stabilizer solution) to the large particle size catalyst precursor obtained in step (2), stabilize it at 25℃ for 24h, and then wash and dry it to obtain platinum manganese alloy catalyst.
[0036] Single-cell fabrication: Accurately weigh 200 mg of the prepared alloy catalyst; measure 20 mL of pure water, 20 mL of isopropanol, and 2 mL of perfluorosulfonic acid resin solution, add them to the catalyst, and disperse thoroughly for 1 hour to form catalyst ink. Coat the catalyst ink evenly onto the cut proton exchange membrane, designating it as the cathode; similarly, weigh platinum-carbon catalyst (JM9100) and coat it on the other side of the membrane, designating it as the anode, forming the membrane electrode assembly; the gas diffusion layer uses SGL 28BC model GDL. Disassemble the balticFuelCells QCF25 quick-assembly test fixture, and sequentially place the thickness limit sheet, the first GDL, the CCM, and the second GDL. After securing them, rotate the pneumatic button to complete the clamping. After connecting the gas pipeline, perform an airtightness test. If the airtightness is satisfactory, conduct a single-cell test.
[0037] Single cell test conditions: Single cell area 25cm² 2 The stoichiometric ratio of anode to cathode is 1.5:2.0, the humidity of anode and cathode is 50%, the anode feed pressure is 1.6 bar, the cathode feed pressure is 1.5 bar, and the battery test temperature is 80℃.
[0038] Example 2
[0039] A method for preparing a large-particle-size alloy catalyst differs from Example 1 in that step (1) uses a planetary ball mill (model: MSK-SFM-1) for uniform mixing, while other raw materials and proportions remain the same as in Example 1. The method and testing conditions for fabricating a single cell using the alloy catalyst prepared in this example are the same as in Example 1.
[0040] Example 3
[0041] A method for preparing a large-particle-size alloy catalyst includes the following steps:
[0042] (1) Grind 106g of chloroplatinic acid hexahydrate crystals, 14.9g of manganese nitrate tetrahydrate and 20g of Ketjen black carrier evenly in a ball mill, then add 24.6g of urea and 4g of sodium hydroxide mixture and continue ball milling evenly. Sieve through a 50-mesh sieve to obtain a uniformly mixed raw material.
[0043] (2) The raw materials that were mixed evenly in step (1) were heated to 1300°C for 3 hours in a mixed atmosphere of hydrogen and argon (the volume ratio of hydrogen in the mixed atmosphere was 5%) at a heating rate of 30°C / min. After the calcination was completed, a large particle size catalyst precursor was obtained.
[0044] (3) Add 10L of 1mol / L sulfuric acid and citric acid solution (the molar ratio of sulfuric acid to citric acid is 3:1) to the large particle size catalyst precursor obtained in step (2), stabilize it at 80℃ for 6h, and then wash and dry it to obtain the alloy catalyst.
[0045] Single cell fabrication: The fabrication method and testing conditions for single cells using the alloy catalyst prepared in this embodiment are the same as those in Example 1.
[0046] Example 4
[0047] A method for preparing a large-particle-size alloy catalyst is disclosed. The difference between this embodiment and Example 2 is that the calcination temperature in step (2) is 1000℃, and the stabilizer solution in step (3) is a 4 mol / L hydrochloric acid-ethylene glycol solution. Other raw materials and proportions are the same as in Example 2. The method and testing conditions for fabricating a single cell using the alloy catalyst prepared in this embodiment are the same as in Example 2.
[0048] Example 5
[0049] A method for preparing a large-particle-size alloy catalyst is disclosed. The difference between this embodiment and Example 3 is that in step (1), platinum nitrate is used as the noble metal raw material, and a mixed support of 80% Ketjen black and 20% acetylene black by mass fraction is used. The calcination temperature in step (2) is 1200℃. The stabilizer solution in step (3) is a 1 mol / L solution of sulfuric acid and citric acid in ethylene glycol. Other raw materials and proportions are the same as in Example 3. The method and testing conditions for fabricating a single cell using the alloy catalyst prepared in this embodiment are the same as in Example 3.
[0050] Example 6
[0051] A method for preparing a large-particle-size alloy catalyst is disclosed. The difference between this embodiment and Example 5 is that in step (1), dinitrosodiammineplatinum is used as the noble metal raw material, and manganese stearate is used as the manganese source. The calcination temperature in step (2) is 1100℃. The stabilizer solution in step (3) is a 2 mol / L nitric acid and citric acid (the molar ratio of nitric acid to citric acid is 1:4) ethylene glycol solution. Other raw materials and proportions are the same as in Example 5. The method and testing conditions for fabricating a single cell using the alloy catalyst prepared in this embodiment are the same as in Example 5.
[0052] Comparative Example 1
[0053] A method for preparing an alloy catalyst is described. The difference between this comparative example and Example 6 is that the temperature in step (2) is 550°C, while the other raw materials and proportions are the same as in Example 6. The method and testing conditions for fabricating a single cell using the alloy catalyst prepared in this example are the same as in Example 6.
[0054] Table 1. Comparison of relevant properties of the alloy catalysts prepared in Examples 1-6 and the comparative examples.
[0055]
[0056] *The XRD particle size of the alloy catalyst prepared in this invention was calculated according to the Scherrer equation; Electrochemical performance testing conditions: three-electrode system, electrolyte is oxygen-saturated 0.1M HClO4; Rotation speed: 1600 rpm; Scan rate: 10 mV / s -1 ;
[0057] As can be seen from Table 1, the XRD calculated particle size of Examples 1-6 is all above 12nm. Among them, Example 3 has the largest particle size and its mass activity can reach 441mA / mg, which is 3 times higher than the mass activity value of 130mA / mg of the commercially available platinum-carbon catalyst JM9100. The higher the mass activity, the better the oxygen reduction performance, and the better the performance when applied to the cathode side of the fuel cell.
[0058] from Figure 1 It can be seen that the alloy particles in Example 4 are aggregated and have a relatively large particle size in the microscopic transmission electron microscope image.
[0059] from Figure 2 It can be seen that the XRD pattern of the alloy catalyst prepared in Example 3 has a narrower half-peak width than that of Comparative Example 1, and therefore the particle size calculated according to the Scherrer formula is larger.
[0060] from Figure 3 It can be seen that the fuel cell single cells fabricated using the large-particle-size alloy catalysts prepared by the methods in Examples 5 and 6 of this invention can all achieve a current density of 1.95 A / cm² at 0.65 V. 2The power density can reach 1.28 W / cm². 2 This is higher than the current mainstream power density of 1W / cm³ in China. 2 The level.
[0061] from Figure 4 It can be seen that the MA value of the large-particle-size alloy catalyst prepared by Example 5 of the present invention decreased from 418 mA / mg to 401 mA / mg before and after 30,000 cycles of catalyst durability test, with a performance reduction of 4.07%, and the attenuation is very small, indicating that the catalyst has excellent oxygen reduction durability.
[0062] Therefore, the large-particle-size alloy catalyst prepared by the method of the present invention has high oxygen reduction activity, and the large particle size does not affect its performance in single-cell applications. It has high power density and better battery performance.
[0063] Finally, it should be noted that the above specific embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.
Claims
1. A method for preparing a large-particle-size alloy catalyst, characterized in that, Includes the following steps: (1) Raw material mixing: Add the calculated amount of precious metal compound and transition metal powder to the carrier, mix thoroughly and evenly, and then add the mixing agent and mix thoroughly and evenly; (2) Particle size growth: The raw materials that are mixed evenly in step (1) are calcined in a mixed atmosphere for 3-18 hours. After calcination, a catalyst precursor with large particle size is obtained. (3) Particle size stabilization step: Add 0.5-20L of a stabilizer solution with a concentration of 1-4mol / L to the large particle size catalyst precursor obtained in step (2), stabilize it at 25-80℃ for 1-24h, and then wash and dry it to obtain the alloy catalyst. The specific surface area of the carrier mentioned in step (1) is 500-1500 m². 2 / g, using carriers including Ketjen black, nano-graphite, conductive carbon black, mesoporous carbon materials, carbon nanotubes and graphene. The noble metal compound mentioned in step (1) refers to a platinum-containing compound including chloroplatinic acid, platinum nitrate, dinitrosodiamineplatinum, and platinum chloride, with a mass ratio of noble metal element to carrier of 0.1-1.
2. The transition metal powder mentioned in step (1) refers to manganese-containing compounds including manganese sulfate, manganese nitrate, manganese acid phosphate, manganese dioxide, manganese carbonate and manganese stearate, with a mass ratio of transition metal element to carrier of 0.03-0.
5. The mixed atmosphere mentioned in step (2) is a mixture of hydrogen and argon, wherein the volume percentage of hydrogen in the mixed atmosphere is 50 ppm-5%; In step (2), the temperature is increased to 900-1300℃ at a heating rate of 5-30℃ / min during roasting.
2. The method for preparing the large-particle-size alloy catalyst according to claim 1, characterized in that, The mixture in step (1) is one of potassium hydroxide, potassium carbonate, urea, sodium hydroxide, sodium carbonate, sodium bicarbonate and ammonium dihydrogen phosphate or any mixture of the above substances, and the mass of the mixture accounts for 0.01-3% of the total mass of the raw materials.
3. The method for preparing the large-particle-size alloy catalyst according to claim 1, characterized in that, The stabilizer solution mentioned in step (3) is a mixture of two or more of ethylene glycol, ethanol, hydrochloric acid, nitric acid, citric acid, sulfuric acid, acetic acid and water, with the largest molar amount as the solvent, and the concentration of the stabilizer solution is 1-4 mol / L.
4. A large-particle-size alloy catalyst, characterized in that, The large-particle-size alloy catalyst was prepared by the preparation method according to any one of claims 1-3. Based on the XRD pattern, the particle size of the catalyst was calculated using the Scherrer formula to be ≥12nm.
5. The application of the large-particle-size alloy catalyst according to claim 4 in fuel cells.
Citation Information
Patent Citations
Carbon-containing metal catalyst, preparation method and application thereof
CN103227334A
Catalyst for solid polymer fuel cell and method for producing same
CN104412431A